Echocardiographic assessment of right ventricular function in experimental pulmonary hypertension. (June 2019) - Zhu, Zhongkai; Godana, Dureti; Li, Ailing; Rodriguez, Bianca; Gu, Chenxin; Tang, Haiyang; Minshall, Richard D.; Huang, Wei; Chen, Jiwang
Echocardiography, a non-invasive and cost-effective method for monitoring cardiac function, is commonly used for evaluation and pre-clinical diagnostics of pulmonary hypertension (PH). Previous echocardiographic studies in experimental models of PH are fragmentary in terms of the evaluation of right ventricle (RV) function. In this study, three rodent models of PH: a mouse model of hypoxia-induced PH, a rat model of hypoxia+Sugen induced PH and a rat model of monocrotaline-induced PH, were employed to measure RV fractional area change (RVFAC), RV free wall thickness (RVFWT), pulmonary acceleration time (PAT), pulmonary ejection time (PET), and tricuspid annular plane systolic excursion (TAPSE). We found that, in these models, RVFWT significantly increased, but RVFAC, PAT, or PAT/PET ratios and TAPSE values significantly decreased. Accurate and complete TAPSE patterns were demonstrated in the three rodent models of PH. The RV echocardiography data matched the corresponding invasive hemodynamic and heart histologic data in each model. This serves as a reference study for real-time and non-invasive evaluation of RV function in rodent models of PH using echocardiography.